Supply base innovation and firm financial performance - Dong, Yan; Skowronski, Keith; Song, Sining; Venkataraman, Sriram; Zou, Fan (Journal of Operations Management, 2020)
AbstractFirms are increasingly sourcing innovation from their supply chain partners. Meanwhile, supply chains have evolved into complex networks, which complicates the role that supply chain partners play in innovation and financial performance of firms. Previous research has mainly focused on the direct effect of innovation on a firm's financial performance, overlooking the innovativeness and complexity of supply networks. In this research, we focus on a firm's supply base, defined as the first tier of a supply network, and investigate the relationship between the intensity of R&D within the supply base and the financial performance of the focal firm. We also examine the moderating role of three aspects of supply base complexity—Number of suppliers, differentiation, and inter‐relationships among suppliers. Utilizing secondary data from Bloomberg and Compustat, we find that the R&D intensity of a firm's supply base is positively associated with the firm's financial performance. Further, all three aspects of supply base complexity negatively moderate this relationship. These findings make important contributions to the literature by establishing a direct, positive relationship between supply base R&D and firm financial performance, which is attenuated by complexities within the supply base.